Response of kikuyu grass (Pennisetum clandestinum) to irrigation with saline, sodic wastes and nitrogenous, manganiferous effluent - Mills, Anthony (Department of Geological Sciences, 2017)
The Manganese Metal Company (MMC) situated in Nelspruit, Eastern Transvaal, South Africa produces a manganiferous saline effluent from a manganese ore leaching process. The high NH₄ content of the waste has been identified as a possible nitrogen fertilizer source. Irrigation of the MMC waste over nearby kikuyu ( Pennisetum clandestinum) pastures could thus potentially solve a waste disposal problem as well as provide fertilization of the pastures, although the high manganese content of the waste poses a risk of manganese toxicity or pollution. The kikuyu pastures are presently used as a land disposal system for a saline waste from a pulp bleaching process. Due to process changes, the dominant salt type in the waste is anticipated to change from KaCl to Na₂SO₄. Pot experiments with kikuyu were undertaken to investigate NaCl versus Na₂SO₄ salinity effects, Mn toxicity threshold levels and MMC waste versus a standard nitrogen fertilizer (NH₄NO₃) yield response. The results demonstrated that kikuyu grass is both salinity and Mn tolerant. Kikuyu salinity tolerance, using electrical conductivity as a salinity index, was significantly greater in NaCl than Na₂SO₄ salinity. This difference was attributed to the formation of SO₄ neutral ion pairs in Na₂SO₄ treatments which decreased cation uptake, increased osmotic stress relative to electrical conductivity and led to a possible SO₄-induced Ca deficiency. Cl adsorption in manganous sulphate and Na₂SO₄ treated soils was speculatively attributed to the formation of an undocumented ettringite-like mineral. Kikuyu exhibited both a fertilization effect and a Mn toxicity effect with manganous sulphate applications. An increase in yield occurred between Mn applications of 800 and 1600 mg/kg soil. This effect was attributed to increased nutrient availability as a result of nitrogen mineralisation and soil desorption processes. Mn applications of 3200 and 8000 mg/kg resulted in severe Mn toxicity symptoms and reductions in yield. Fertilization of kikuyu with NH₄NO₃ and MMC waste produced similar yield responses. Manganese toxicity did not manifest itself in MMC waste treated kikuyu, even at nitrogen loadings of 800 kgN/ha. Manganese attenuation in the soil by MnCO₃ precipitation, oxidation of Mn²⁺ and Mn adsorption are expected to prevent excess Mn²⁺ accumulation which would pose a Mn toxicity and water pollution risk. The disposal of untreated MMC waste as a nitrogen fertilizer substitute for kikuyu pastures is thus in principle a feasible operation in terms of maintaining pasture sustainability and preventing pollution of water resources.